Quantitative competitive PCR with bronchoalveolar lavage fluid for diagnosis of toxoplasmosis in AIDS patients. - Bretagne, S (1995)
Of 121 AIDS patients, 12 (10%) had Toxoplasma gondii DNA detected by competitive PCR in their bronchoalveolar lavage samples. Quantitation of the PCR results showed a correlation between the parasite burden and the serum lactic dehydrogenase titer. Quantitative competitive PCR could be useful to assess the diagnosis and the severity of pulmonary toxoplasmosis.